2012
DOI: 10.1590/s0104-77602012000400016
|View full text |Cite
|
Sign up to set email alerts
|

Utilização do teste de raios - x na avaliação dos efeitos da dessecação e infestação em diásporos de Canela-Batalha - Cryptocarya aschersoniana Mez (Lauraceae)

Abstract: RESUMO:No presente trabalho, objetivou-se avaliar os efeitos da dessecação e identificar lesões por predação por insetos, em diásporos de canela-batalha (Cryptocarya aschersoniana Mez.), utilizando-se testes de raios X. Os danos provocados pela dessecação foram dimensionados nas imagens e associados à formação de plântulas. Diásporos recém-beneficiados (45 % de umidade e 37 % de germinação) foram colocados para secar em sala climatizada (20 °C e 60 % UR), dentro de bandejas plásticas em camada única. Posterior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 12 publications
2
7
0
1
Order By: Relevance
“…When one of the internal seed structures was not complete, the chances of the formation of either low-vigor seedlings or no seedlings increases (Nunes et al, 2014). Muxfeldt et al (2012) also found a higher percentage of seeds with internal voids or malformations in desiccated seeds of Cryptocarpa aschersoniana Mez (Lauraceae); however, this characteristic did not result in reduced germination, as observed in this study. This can be explained by the deleterious effects that drying could have caused to the internal morphology of the seeds, which can also be seen in the different percentage of filled seeds among the various water contents (Table 1).…”
Section: Resultssupporting
confidence: 64%
“…When one of the internal seed structures was not complete, the chances of the formation of either low-vigor seedlings or no seedlings increases (Nunes et al, 2014). Muxfeldt et al (2012) also found a higher percentage of seeds with internal voids or malformations in desiccated seeds of Cryptocarpa aschersoniana Mez (Lauraceae); however, this characteristic did not result in reduced germination, as observed in this study. This can be explained by the deleterious effects that drying could have caused to the internal morphology of the seeds, which can also be seen in the different percentage of filled seeds among the various water contents (Table 1).…”
Section: Resultssupporting
confidence: 64%
“…Cryptocarya aschersoniana seeds are sensitive to desiccation Muxfeldt et al 2012); therefore, their water content must remain high after dispersal to ensure their viability, with the critical water content near 28%, and the lethal water content between 18.1% and 21.5% (Tonetti 2013). In this study, the seeds that were used to establish the seed banks had water contents above 43%.…”
Section: Discussionmentioning
confidence: 99%
“…(Lauraceae) is a tropical tree species, widely distributed across Brazil, where it is known as 'canela-batalha' (Lorenzi 1998;Moraes 2007). This species belongs to the climax ecological group (Davide et al 1995) and produces seeds sensitive to desiccation Muxfeldt et al 2012). It is considered an ecologically important species because its fruits are consumed by several species of animals, which also act as seed dispersers (Lorenzi 1998).…”
Section: The Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…The growing demand for seeds of native forest species, through production and conservation programs, has generated the need to develop technologies for evaluating the quality of these seeds (Carvalho et al, 2009) to make sure that they will originate healthy plants, since obtaining and maintaining high physiological quality of a seed lot is a critical step in the production of seedlings (Muxfeldt et al, 2012).…”
Section: Introductionmentioning
confidence: 99%